The use of digital media in education: from perspective to practice (Research, Society and Development, 2020)
Technological evolution is a constant in all contemporary social activities. Despite this, the school methodology remains, with rare exceptions, without significant changes in relation to the use of Digital Technologies. This article is a proposal for reflection on pedagogical practice in order to understand it in the context of the initial and continuing education of educators, showing the use of TDIs as essential pedagogical tools in the current context. The investigation was developed under a qualitative ethnographic approach, using the action research process in the participant observation modality. The production of information involves the observation of practical activities with the use of technologies, interviews and document analysis, with the interpretation by the data triangulation process. The discussions highlight the standardization of the methodology for transmitting content through memorization and learning through the repetition of ready-made concepts. The results indicate expository classes and the use of the textbook and the blackboard as resources most used by teachers in the classroom. The suspension of face-to-face classes due to the Pandemic, evidenced the more accentuated use of digital resources in teaching due to the modality of remote classes. The final considerations point to the relevance of the theme in the current educational scenario and emphasize the importance of the teacher seeking training and modernizing his practice in order to use the technologies for his own growth and that of the student, promoting the appropriate use of Digital Information Technologies and Communication in the context of meaningful, dynamic and transformative learning.